METHODS FOR THE SYNTHESIS OF AROMATIC OLIGESTERS - Rayimov Zukhriddin Khayriddin ugli; Khaitov Sadullo Toyir ugli (Journals Park Publishing, 2024)
Due to the fact that the problem of creating thermostable polymers with high fire resistance and good physical and mechanical properties is very relevant today for various fields of technology, depending on the structure of the starting materials, the production of copolyesters and block copolyesters based on oligosulfoneketone, oligosulfone, oligoketone and oligoformal. It is important from a scientific and practical point of view to study the laws of formation, to determine the relationship between the structure, composition and properties of copolymers.
Keywords: oligosulfoketones (OSK), oligoketones (OC), oligosulfones (OS), dimethyl sulfoxide (DMSO), degree of polycondensation, disodium salt, dipolar solvent.